Chyawanprash, An Ancient Indian Ayurvedic Medicinal Food, Regulates Immune Response in Zebrafish Model of Inflammation by Moderating Inflammatory Biomarkers - Balkrishna, Acharya; Tomer, Meenu; Manik, Moumita; Srivastava, Jyotish; Dev, Rishabh; Haldar, Swati; Varshney, Anurag (Frontiers in Pharmacology, 2021)
The time-tested Ayurvedic medicinal food, Chyawanprash has been a part of Indian diet since ancient times. It is an extremely concentrated mixture of extracts from medicinal herbs and processed minerals, known for its immunity boosting, rejuvenating and anti-oxidative effects. In this study, we have evaluated the anti-inflammatory potential of Patanjali Special Chyawanprash (PSCP) using zebrafish model of inflammation. Zebrafishes were fed on PSCP-infused pellets at stipulated doses for thirteen days before inducing inflammation through lipopolysaccharide (LPS) injection. The test subjects were monitored for inflammatory pathologies like, behavioral fever, hyperventilation, skin hemorrhage, locomotory agility and morphological anomaly. PSCP exerted a strong prophylactic effect on the zebrafish that efficiently protected them from inflammatory manifestations at human equivalent dose. Expression levels of pro-inflammatory cytokines, like, interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α) and interleukin-1 beta (IL-1β) were also reduced in the LPS-stimulated zebrafish fed on PSCP infused pellets. Skin hemorrhage, hyperventilation and loss of caudal fins are characteristics of LPS induced inflammation in zebrafish. PSCP prophylactically ameliorated skin hemorrhage, restored normal respiration and prevented loss of caudal fin in inflamed zebrafishes. Under in vitro conditions, PSCP reduced IL-6 and TNF-α secretion by THP-1 macrophages in a dose-dependent manner by targeting NF-κB signaling, as evident from the Secreted Embryonic Alkaline Phosphatase (SEAP) reporter assay. These medicinal benefits of PSCP can be attributed to its constitutional bioactive components. Taken together, these observations provide in vivo validation of the anti-inflamamtory property and in vitro insight into the mode-of-action of Chyawanprash, a traditionally described medicinal food.